Multi-drug loaded gastric-floating microcapsules - Tan, Nicholas Chaoyang (2014)
Floating drug delivery system (FDDS) was introduced to overcome physiological difficulties, such as unpredictable gastric emptying process (GET) and short gastric residence times (GRT) by prolonging the GRT. However, studies had proven that most hydrophobic drugs achieved very low and incomplete release within the gastrointestinal (GI) residence period, approximately 10 hours for FDDS. Therefore this study aimed to control drug release in floating microcapsules that integrate both hydrophilic and hydrophobic drug within the system. This study modified a microcapsule fabrication process to simultaneously release both hydrophilic drug (metformin) and hydrophobic drug (fenofibrate), in a controlled and sustained manner, with an objective to further increase hydrophobic drug release rate. The previous study using solvent evaporation method to fabricate multi-drug gastric floating microcapsules yielded 86% metformin release but only 20% fenofibrate release in 10 hours. The modified fabrication process in this study introduced a spray-coating technique which achieved close to 100% metformin release and also 100% fenofibrate release within 10 hours with parameter variations.